Gerakan Sosial Baru di Ruang Publik Virtual - Fuadi, Abdulloh; Tasmin, Tasmin (Hanifiya: Jurnal Studi Agama-Agama, 2018)
The era of information technology that has developed dynamically in recent years has brought significant changes in the way to communicate and mobilize the masses. Public spaces that were once confined to a certain space and time, are now eliminated by the latest technology, to give birth to unlimited public space and can be accessed by anyone, anywhere and anytime. Public space is called virtual public space. The sophistication and effectiveness of this virtual public space is increasingly apparent when a new social movement is able to use it. One of the new social movements was called the National Movement for Guards Fatwa (GNPF) of the Indonesian Ulama Council (MUI) which was born around the end of 2016. This paper tried to examine the MUI GNPF as a new social movement that managed to make maximum use of virtual public space. Felt until now, a year later. In general, this paper is divided into two. The first part discusses the actions of the MUI's GNPF and a series of Islamic Defending Action. The second part discusses virtual public space which is used as the main means for the GNPF MUI in its movement to mobilize the masses.